The Role of Healthy Diets in Environmentally Sustainable Food Systems. Issue 2 (December 2020) - Clark, Michael; Macdiarmid, Jennie; Jones, Andrew D.; Ranganathan, Janet; Herrero, Mario; Fanzo, Jessica
Background: The global food system is directly linked to international health and sustainability targets, such as the United Nation's Sustainable Development Goals, Paris Agreement climate change targets, and the Aichi Biodiversity Targets. These targets are already threatened by current dietary patterns and will be further threatened by 2050 because of a growing population and transitions toward diets with more calories, animal-source foods, and ultra-processed foods. While dietary changes to healthier and predominantly plant-based diets will be integral to meeting environmental targets, economic, social, and cultural barriers make such dietary transitions difficult. Objective: To discuss the role of healthy diets in sustainable food systems and to highlight potential difficulties and solutions of transitioning toward healthier dietary patterns. To do so, we synthesize global knowledge and conduct a series of case studies on 4 countries that differ in their social, economic, political, and dietary contexts: Brazil, Vietnam, Kenya, and Sweden. Conclusions: No single "silver bullet" policy solution exists to shift food choices toward sustainable healthy diets. Instead, simultaneous action by the public sector, private sector, and governments will be needed.